Effects of dietary chromium picolinate supplementation on broiler growth performance: A meta-analysis - Feng, Chao (PLoS One, 2021)
OBJECTIVE: A meta-analysis was conducted to assess the effects of dietary chromium picolinate (CrPic) supplementation on broiler growth performance and to determine whether such effects are regulated by broiler strains, sex, environmental stress, or contextual factors including study area and years. METHODS: Eligible studies were identified by searching the Web of Science, Springer, Elsevier, ScienceDirect, Taylor & Francis Online databases. Weighted average differences with corresponding 95% confidence intervals were computed with a random-effects model. We performed subgroup analysis stratified by study area, published years, broiler strains and sex, and environmental stress. Publication bias was assessed with Egger’s test method. A total of 15 studies eligible for inclusion. RESULTS: The results indicated that CrPic supplementation significantly improved broiler growth performance and subgroup analysis confirmed this conclusion. We also found that Ross 308 or male broilers might be more sensitive to CrPic supplementation and showed better growth performance. A model was used to obtain the amount of chromium addition under the optimal growth performance, which suggested that the maximum value of average daily gain (ADG) was reached when chromium addition was 1810 μg/kg. The results of the sensitivity analysis showed low sensitivity and high stability of the meta-analysis. CONCLUSIONS: CrPic supplementation had a positive effect on the growth performance of broilers, and this meta-analysis provides a more accurate value of chromium addition, which may be beneficial for the practice of the broiler industry.